1982
DOI: 10.1021/ic00132a045
|View full text |Cite
|
Sign up to set email alerts
|

Electron-transfer reactions of ion pairs: reductions of various substituted pyridinepentaamminecobalt(III) complexes by hexacyanoferrate(II)

Abstract: Supplementary Material Available: Two tables of kinetic data (Tables II and IV) (3 pages). Ordering information is given on any current masthead page.(43) Foxman, B. M.; Merit, A. J.; Marzilli, P. A.; Sargeson, A. M., to be submitted for publication. A preliminary account is given in ref 4, p 328.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…This reaction is postulated as outer-sphere in comparison with such type of reactions in the literature (Miralles et al, 1982) involving ordinary lower primary amine coordinated cobalt(III) complexes similar to the surfactant cobalt(III) complexes of the present study. The complexes of the present study are inert to substitution due to the non-availability of Microheterogeneous mediated electron transfer reaction (ETR) of surfactant cobalt(III) complexes by Fe 2+ a co-ordination site for inner-sphere precursor complex.…”
Section: Electron-transfer Kineticssupporting
confidence: 56%
“…This reaction is postulated as outer-sphere in comparison with such type of reactions in the literature (Miralles et al, 1982) involving ordinary lower primary amine coordinated cobalt(III) complexes similar to the surfactant cobalt(III) complexes of the present study. The complexes of the present study are inert to substitution due to the non-availability of Microheterogeneous mediated electron transfer reaction (ETR) of surfactant cobalt(III) complexes by Fe 2+ a co-ordination site for inner-sphere precursor complex.…”
Section: Electron-transfer Kineticssupporting
confidence: 56%
“…'~ Values of the radii for the anionic and cationiccomplexes listed in Table I1 fall in the ranges higher (by factors of 4 to 10) than the values calculated from Eq. (7). It has been ~u g g e s t e d~.~.…”
Section: N N D 3 3000mentioning
confidence: 99%
“…On mixing Fe(CN) 6 4− and our surfactant cobalt(III) complexes in the aqueous solution, a precipitate was formed and, therefore, homogeneous kinetic measurements were precluded. However, when Na 2 H 2 EDTA was present in the solution, no precipitate was formed during the reaction and therefore all the experiments were carried out in the presence of Na 2 H 2 EDTA . A disodium salt of ethylenediamine tetraacetic acid acted as a sequestering agent to remove cobalt(II) and prevented the precipitation of the cobalt(II) ion as a hexacyanoferrate salt.…”
Section: Methodsmentioning
confidence: 99%
“…The ion pairing of the complexes with macrocycle STCA accelerates the Fe(CN) 6 4− –cobalt(III) electron‐transfer reactions. Miralles et al have reported the outer‐sphere reductions of pyridinepentamminecobalt(III) and pyridinepentammineruthenium(III) complexes by hexacyanoferrate(II). They have discussed the mechanisms of these reactions on the basis of Marcus' equation, electrostatic effects, and orbital considerations.…”
Section: Introductionmentioning
confidence: 99%